Buenos Aires, Londres, New Jersey : Errico Malatesta, engagement et vie transnationale d’un Italien anarchiste - Davide Turcato (Cahiers d’histoire.)
The exile life of Errico Malatesta (1853-1932), one of the best-known anarchists worldwide, lends itself to different interpretations. The quixotic and ultimately irrationalistic one favoured by mainstream historiography looks upon the anarchists’ wanderings as those of uprooted knights errant always at the mercy of events. In contrast, I analyse anarchist exile in the context of Italian migration, through the life of a key figure. In this light, anarchist exile no longer seems an aimless wandering, but rather a seamless and dense web of movements within a transnational community that comprised the Mediterranean Sea and the Atlantic Ocean. On the one hand, the study of anarchist exile adds to our understanding of Italian migration. Anarchist exile represented only a fraction of that migration, but it was a culturally significant component, which added its own dynamics to those of migration at large. On the other hand, the study of migration deepens our understanding of anarchism as a political project that deliberately relied on migration to supply lifeblood to a prolonged struggle in the homeland.